Prva dijalektologija crnogorskoga jezika: Adnan Čirgić, Dijalektologija crnogorskoga jezika, FCJK, 2017 - Vujović, Novica (Slavia Centralis, 2020)
The article presents the first dialectology of the Montenegrin language (Dialectology of the Montenegrin language, original name: Dijalektologija crnogorskoga jezika, 2017), authored by linguist Adnan Čirgić.